The reconstruction of the quartic Bezier curve using uniform parameterisation / Siti Sarah Raseli ... [et al.] - Raseli, Siti Sarah; Mahat, Norpah; Wan Muhammad Shafawi, Wan Nur Ashilah; Ramli, Ahmad (Unit Penerbitan UiTM Kelantan, 2024)
This study proposes the reconstruction of a higher Bezier curve using uniform parameterisation to improve the design of a curve. The parameterisation process is the key element in the reconstruction of the curve. The reconstruction process starts by selecting an image. Next, the boundary is extracted from the image. Using uniform parameterisation, the parameter value of the image is determined. Then, new control points for the image are calculated. In the next stage, the construction of the image is implemented. The finding displays an improved reconstruction compared to the initial curve. The reconstruction proposed in this study is provided with systematic and scientific techniques that can benefit designers, businesses, and the craft industry. This proposed study can also enhance the creativity and innovation of the design industry.